Live-cell multiphoton fluorescence correlation spectroscopy with an improved large stokes shift fluorescent protein - Guan, Yinghua; Meurer, Matthias; Raghavan, Sarada; Kats, Ilia; Knop, Michael (Molecular biology of the cell, 2015)
An improved variant of mKeima, a monomeric long Stokes shift red fluorescent protein, is introduced, called hmKeima8.5. Its increased intracellular brightness and long Stokes shift (~180 nm) make it an excellent partner with teal fluorescent protein (mTFP1) for multiphoton, multicolor applications. Here we demonstrate its utility in intracellular fluorescence correlation spectroscopy applications., We report an improved variant of mKeima, a monomeric long Stokes shift red fluorescent protein, hmKeima8.5. The increased intracellular brightness and large Stokes shift (∼180 nm) make it an excellent partner with teal fluorescent protein (mTFP1) for multiphoton, multicolor applications. Excitation of this pair by a single multiphoton excitation wavelength (MPE, 850 nm) yields well-separable emission peaks (∼120-nm separation). Using this pair, we measure homo- and hetero-oligomerization interactions in living cells via multiphoton excitation fluorescence correlation spectroscopy (MPE-FCS). Using tandem dimer proteins and small-molecule inducible dimerization domains, we demonstrate robust and quantitative detection of intracellular protein-protein interactions. We also use MPE-FCCS to detect drug-protein interactions in the intracellular environment using a Coumarin 343 (C343)-conjugated drug and hmKeima8.5 as a fluorescence pair. The mTFP1/hmKeima8.5 and C343/hmKeima8.5 combinations, together with our calibration constructs, provide a practical and broadly applicable toolbox for the investigation of molecular interactions in the cytoplasm of living cells.
Gesehen am 08.08.2017